1982
DOI: 10.1002/ijc.2910300303
|View full text |Cite
|
Sign up to set email alerts
|

Cellular ingestion, toxic effects, and lesions observed in human bronchial epithelial tissue and cells cultured with asbestos and glass fibers

Abstract: Although exposure to asbestos has been shown in previous epidemiological studies to synergistically increase the risk of bronchogenic carcinoma for cigarette smokers, the pathobiological machanism(s) responsible for the cocarcinogenic action of asbestos is not known. Therefore, the effects of asbestos fibers on normal human tracheobronchial epithelium are of interest. Asbestos fibers, ie., amosite, crocidolite and chrysotile (UICC samples) and glass fibers were initially assayed for their cytotoxicity. Bronchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Chrysotile was the most cytotoxic fiber tested and even glass fibers were markedly toxic (chrysotile, 0.06; amosite, 0.10; crocidolite, 0.40; glass fibers, 1.02). Thus, the mesothelial cells were significantly more sensitive to asbestos and glass fibers than were previously tested normal human lung cells-i.e., the amosite 50o cytotoxic doses for bronchial epithelial and bronchial fibroblastic cells were 1.02 and 10.40 ,g of fibers per cm2 of culture dish surface area, respectively (18).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Chrysotile was the most cytotoxic fiber tested and even glass fibers were markedly toxic (chrysotile, 0.06; amosite, 0.10; crocidolite, 0.40; glass fibers, 1.02). Thus, the mesothelial cells were significantly more sensitive to asbestos and glass fibers than were previously tested normal human lung cells-i.e., the amosite 50o cytotoxic doses for bronchial epithelial and bronchial fibroblastic cells were 1.02 and 10.40 ,g of fibers per cm2 of culture dish surface area, respectively (18).…”
Section: Resultsmentioning
confidence: 95%
“…In fact, although exposure to chemicals and radiation has produced mesothelioma in experimental animals (1), no etiologic agent other than fibrous structures-i.e., zeolites, ceramics, and occasionally glasshas been identified as a causative agent for human pleural and peritoneal mesothelioma (1)(2)(3). Mesothelial cells actively ingest asbestos in a manner analogous to human bronchial epithelial cells (18), but the resultant effects are markedly more cytotoxic. This observation suggests that the mesothelial cell has unusual properties that increase its sensitivity to fibrous agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the cell-associated fibers were assumed to be within phagosomes by virtue of the cells phagocytic activity and light microscopic appearance. In addition, fibers or particles have been detected in alveolar macrophages (10), type I epithelial cells (1,13,14), type II epithelial cells (1,15), tracheobronchial cells (16,17), and pleural mesothelial cells (18).…”
Section: Fa"00mentioning
confidence: 99%
“…In vitro acellular systems have been developed to study the release of chemicals from fibers in conditions close to the physiological status (13)(14)(15)(16) (24) and an easy uptake have been reported (25,26). Fibers longer than the cell and extruding fibers often are noted with different cell types (19,(21)(22)(23). Ex vivo studies have confirmed that particle internalization occurs in vivo (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%